2002
DOI: 10.1177/002215540205000702
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Urotensin-II Immunoreactivity in Normal Human Kidneys and Renal Carcinoma

Abstract: S U M M A R Y Human urotensin-II (U-II) is a cyclic 11-amino-acid residue peptide with a wide range of vasoactive properties dependent on the anatomic site and the species studied. The purpose of this study was to determine the localization of human U-II in normal human kidneys and in renal carcinoma. Normal human kidneys ( n ϭ 11) and eight cases of clear-cell carcinoma were immunostained with a polyclonal antibody to human U-II. In normal human kidneys, U-II was mostly present in the epithelial cells of tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 25 publications
3
63
0
Order By: Relevance
“…More detailed studies have demonstrated that both UII and UT-R are co-expressed in cardiovascular, renal and endocrine tissues (5,23). Recently, UII and UT-R have been identified in some tumor tissues including adrenal tumor (17,18), renal carcinoma (19), and pheochromocytoma (20). In addition, the expression of UII and UT-R has also been found in some tumor cell lines, such as glioblastoma cell line T98G, neuroblastoma cell line IMR32, choriocarcinoma cell line BeWo, adrenocortical carcinoma cell line SW-13, colorectal carcinoma cell line DLD-1, and cervical carcinoma cell line HeLa (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed studies have demonstrated that both UII and UT-R are co-expressed in cardiovascular, renal and endocrine tissues (5,23). Recently, UII and UT-R have been identified in some tumor tissues including adrenal tumor (17,18), renal carcinoma (19), and pheochromocytoma (20). In addition, the expression of UII and UT-R has also been found in some tumor cell lines, such as glioblastoma cell line T98G, neuroblastoma cell line IMR32, choriocarcinoma cell line BeWo, adrenocortical carcinoma cell line SW-13, colorectal carcinoma cell line DLD-1, and cervical carcinoma cell line HeLa (16).…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al (16) showed that UII and UT-R are expressed in glioblastoma cell line T98G, neuroblastoma cell line IMR32, choriocarcinoma cell line BeWo, adrenocortical carcinoma cell line SW-13, colorectal carcinoma cell line DLD-1, and cervical carcinoma cell line HeLa. UII and UT-R mRNA are also expressed in adrenal tumor (17,18), renal carcinoma (19), and pheochromocytoma (20,21). Furthermore, SW-13 cells has been demonstrated to secrete UII (16).…”
Section: Introductionmentioning
confidence: 99%
“…The parent compound pre-pro-UTN is highly expressed in the kidney, and UTN is abundantly represented in endothelial and smooth muscle cells of renal vessels, 38 as well as in tubular cells, and it is excreted in the urine at concentrations substantially higher than the plasma UTN concentration. 39 The kidney synthesizes relevant amounts of UTN, and together with the lung and the liver actively secretes UTN into the systemic circulation.…”
Section: Urotensin In Renal Diseases and In Esrdmentioning
confidence: 99%
“…Urotensin-II-like immunoreactivity was present in the human urine [145]. In the kidney, urotensin-II was expressed in the epithelial cells of tubules and ducts and in the endothelial cells of renal capillaries [146]. Urotensin-II secreted by renal tubular cells into urine may account for urotensin-II-like immunoreactivity in urine.…”
Section: Urotensin-iimentioning
confidence: 97%